1997
DOI: 10.1159/000185472
|View full text |Cite
|
Sign up to set email alerts
|

Pit-1 Gene Expression in Human Pituitary Adenomas

Abstract: The anterior pituitary-specific transcription factor Pit-1 (also known as GHF-1) was initially identified and cloned as a transactivator of the GH and PRL genes, and later as a regulator of the TSHβ gene. Analysis of Pit-1 expression during mouse embryogenesis revealed that initiation of its expression correlates both temporally and spatially with activation of its target genes. Immunocytochemical studies revealed a high expression of Pit-1 protein in the nuclei of only three cell types: somatotropes, lactotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…They are identical in size and sequence in adenomas and in normal pituitary [54], No mutations of Pit-1 gene have been detected in the pitu itary adenomas. Furthermore, the Pit-1 mRNA levels are not quantitatively different in somatotroph and lactotroph adenomas [54][55][56], Pit-1 gene expression was also analyzed in a series of PRL-sccrcting tumors presenting with a variable response to bromocriptine treatment. Quantitative analysis by Northern blot showed that Pit-1 mRNA levels were lower in the tumor presenting with a decreased response to the dopaminergic agonist.…”
Section: Transcription Factor Pit-1mentioning
confidence: 99%
“…They are identical in size and sequence in adenomas and in normal pituitary [54], No mutations of Pit-1 gene have been detected in the pitu itary adenomas. Furthermore, the Pit-1 mRNA levels are not quantitatively different in somatotroph and lactotroph adenomas [54][55][56], Pit-1 gene expression was also analyzed in a series of PRL-sccrcting tumors presenting with a variable response to bromocriptine treatment. Quantitative analysis by Northern blot showed that Pit-1 mRNA levels were lower in the tumor presenting with a decreased response to the dopaminergic agonist.…”
Section: Transcription Factor Pit-1mentioning
confidence: 99%
“…As in the Brn-4 (Ϫ/Ϫ) mouse, no metabolic changes have been reported in these individuals, but specific metabolic tests might be needed to detect subtle differences. No major abnormalities in the amount or form of Pit-1 transcripts have been observed in these tumors, and Pit-1 mRNA levels seem to be similar in somatotrope and lactotrope adenomas (382,385). No major abnormalities in the amount or form of Pit-1 transcripts have been observed in these tumors, and Pit-1 mRNA levels seem to be similar in somatotrope and lactotrope adenomas (382,385).…”
Section: B Brn-4 Mutations In Humansmentioning
confidence: 82%
“…Interestingly, high expression levels of PIT1 represent a constant feature of human pituitary GH, PRL and TSH adenomas (Asa et al 1993, Delhase et al 1993, Friend et al 1993, Pellegrini et al 1994, Pellegrini-Bouiller et al 1997, and several previous studies suggested a potential role for PIT1 in cell proliferation, the prevention of apoptotic death and the pathogenesis of pituitary tumours (Castrillo et al 1991, Gaiddon et al 1999, Salvatori et al 2002, Pellegrini et al 2006. In fact, microinjection of Pit1 antisense sequences blocks cell growth in the GC somatotroph cell line (Castrillo et al 1991) and dominant-negative mutants of Pit1 reduce cell viability by decreasing the growth rate and inducing apoptosis via a caspaseindependent pathway (Pellegrini et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PIT1, also named GHF1, is a member of the POU transcription factor family (Delhase et al 1996), and plays a key role in the specification, expansion and survival of three specific pituitary cell types (somatotropes, lactotropes and a subset of thyrotropes) during the development of the anterior pituitary (Lefevre et al 1987, Nelson et al 1988, Li et al 1990, and its transcriptional activity on many genes, such as GH, PRL, TSHB, GHRHR and PIT1 itself, is crucial for pituitary gland physiology (Lefevre et al 1987, Nelson et al 1988, Chen et al 1990, Li et al 1990, McCormick et al 1990. Moreover, PIT1 is overexpressed in GH, PRL and TSH pituitary adenomas (Asa et al 1993, Delhase et al 1993, Friend et al 1993, Pellegrini et al 1994, Pellegrini-Bouiller et al 1997.…”
Section: Introductionmentioning
confidence: 99%